International strategies of emerging market firms Standardization in brand management revisited - ERDOĞMUŞ, ZEYNEP İREM (EMERALD GROUP PUBLISHING LTD, 2010)
Purpose - This study aims to develop and test a theoretical model to delineate the effects of target market characteristics, firm characteristics and strategic resources, and product characteristics on standardization decisions in brand management of emerging market firms. The effects of standardization on brand performance in international markets are also to be explored. Design/methodology/approach - The study develops a model based on the extant literature and tests its relevance through a survey of eligible managers in charge of international brand operations of 94 strategic business units in Turkey. Findings - The empirical findings indicate that several factors exist as significant drivers of standardization decisions at various levels of brand management. Interestingly, even though firm characteristics and strategic resources were found to be the most critical drivers of brand performance, standardization versus adaptation approaches did not have any significant impact on strategic brand performance. Originality/value - The study takes a standardization perspective to strategic brand management in international markets and tests it from the perspective of emerging markets.
Keywords: Strategic management; Brand management; International marketing; Emerging markets; Turkey; BUSINESS PERFORMANCE; EXPORT PERFORMANCE; PRODUCT; ORIENTATION; INNOVATION; DETERMINANTS; EXPERIENCES; INTEGRATION; ADAPTATION; VENTURES